(untitled) (Itinerarios Educativos, 2019)
This article is intended to give an account on the Optional Seminar ‘Gender and Comprehensive Sexuality Education in an Interpellation to Sciences and Public Policies’ held in 2018 at the Faculty of Sciences and Humanities, Universidad Nacional del Litoral (FHUC-UNL, for their Spanish initials). This paper shows some lines about the context of the emergence of proposals, pedagogical decisions, didactic dilemmas, and some temporary certainties from the viewpoint of the faculty and retrieving the views of the participating students. Teaching and learning are privileged human practices to rethink about oneself/ ourselves/others in terms of sexual rights, disclosing the matrices which perpetuate homo-lesbo-transphobic sexism as regards bodies, pleasure, and desire, revisiting disciplinary areas, education, and professional practices. The proposal is contextualized in a feminist pedagogical approach that calls for horizontality, collective work, and participation with the freedom required to discuss the addressed issues and even to express different positions. Reflecting on the delivery of this seminar aims at demonstrating that comprehensive sexuality education at university level opens the ways to imagine strategies for building gender and sex justice from professional performance, which is not only desirable but, above all, possible.